Management of Teaching Staff Development at School - Zainal Arifin; Candra Wijaya; Solihah Titin Sumanti (STAI Miftahul Ula Nganjuk, 2024)
This research aims to describe the planning, organization, implementation and supervision of the development of teaching staff at SMP Muhammadiyah 2 Medan. This research uses descriptive research with a qualitative approach. The data sources for this research are the Basic Education Council, the Principal of SMP Muhammadiyah 2 Medan, the Deputy Principal for curriculum and student affairs, the head of administration and teaching staff at SMP Muhammadiyah 2 Medan. Data collection techniques were carried out through in-depth interviews, observation and documentation. Data analysis techniques were carried out using the Miles and Huberman model. Techniques for guaranteeing data validity by means of data triangulation and confirmability. There are four findings in this research, namely: (1) Planning for the development of teaching staff is carried out on three bases, namely: the school's vision and mission, reports on supervision results and the increasingly developing conditions of the times. (2) Organizing the development of teaching staff at SMP Muhammadiyah 2 Medan is a functional organization, carried out by detailing all tasks, work that must be carried out and carried out by each personnel in the school organization in terms of achieving goals. (3) Implementation of the development of teaching staff at SMP Muhammdiyah 2 Medan using two programs, namely On The Job Training and Off The Job Training. (4) Supervision of the development of teaching staff at SMP Muhammadiyah 2 Medan is internal supervision. Internal supervision is supervision carried out by the highest leadership within the organization itself.